Arrays of Ag-nanoparticles decorated TiO2 nanotubes as reusable three-dimensional surface-enhanced Raman scattering substrates for molecule detection - Haichao Zhai; Chuhong Zhu; Xiujuan Wang; Yupeng Yuan; Haibin Tang (Frontiers in Chemistry, 2022)
Three-dimensional surface-enhanced Raman scattering (SERS) substrates usually provide more hot spots in the excitation light beam and higher sensitivity when compared with the two-dimensional counterpart. Here a simple approach is presented for the fabrication of arrays of Ag-nanoparticles decorated TiO2 nanotubes. Arrays of ZnO nanorods were fabricated in advance by a hydrothermal method. Then TiO2 nanotube arrays were achieved by immersing the arrays of ZnO nanorods in an aqueous solution of (NH4)2TiF6 for 1.5 h. Vertically aligned TiO2 nanotube arrays were modified with dense Ag nanoparticles by Ag mirror reaction. High density of Ag nanoparticles decorated on the fabricated TiO2 nanotubes provide plenty of hotspots for Raman enhancement. In addition, the fabricated array of Ag nanoparticles modified TiO2 nanotubes can serve as a reusable SERS substrate because of the photocatalytic activity of the TiO2 nanotubes. The SERS substrate adsorbed with analyte molecules can realize self-cleaning in deionized water after UV irradiation for 2.5 h. The sensitivity of the fabricated SERS substrate was investigated by the detection of organic dye molecules. The detectable concentration limits of rhodamine 6G (R6G), malachite green (MG) and methylene blue (MB) were found to be 10−12 M, 10−9 M and 10−8 M, respectively. The enhancement factor (EF) of the three-dimensional SERS substrate was estimated to be as high as ∼1.4×108. Therefore, the prepared Ag nanoparticles modified TiO2 nanotube arrays have promising potentials to be applied to rapid and trace SERS detection of organic chemicals.